2015
DOI: 10.3109/15376516.2015.1045663
|View full text |Cite
|
Sign up to set email alerts
|

Recovery byN-acetylcysteine from subchronic exposure to Imidacloprid-induced hypothalamic–pituitary–adrenal (HPA) axis tissues injury in male rats

Abstract: Imidacloprid is the most important example of the neonicotinoid insecticides known to target the nicotinic acetylcholine receptor in insects, and potentially in mammals. N-Acetyl-l-cysteine (NAC) has been shown to possess curative effects in experimental and clinical investigations. The present study was designed to evaluate the recovery effect of NAC against Imidacloprid-induced oxidative stress and cholinergic transmission alteration in hypothalamic-pituitary-adrenal (HPA) axis of male rats following subchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Kasson and Hsueh found that nicotine and its agonists exert an inhibitory effect on the 17-alpha hydroxylase, therefore preventing the conversion of pregnenolone and progesterone into precursors of DHEA and androstenedione respectively, thereby inhibiting testosterone synthesis in testis cells [28]. This detrimental effect of IMI on testosterone secretion has been previously reported [5, 25, 29].…”
Section: Discussionmentioning
confidence: 78%
“…Kasson and Hsueh found that nicotine and its agonists exert an inhibitory effect on the 17-alpha hydroxylase, therefore preventing the conversion of pregnenolone and progesterone into precursors of DHEA and androstenedione respectively, thereby inhibiting testosterone synthesis in testis cells [28]. This detrimental effect of IMI on testosterone secretion has been previously reported [5, 25, 29].…”
Section: Discussionmentioning
confidence: 78%
“…TBT up-regulates the cell redox balance in brain areas, such as the hypothalamus, resulting in an increase in the reactive oxygen species (ROS) and cellular damage (30,114). Annabi et al (115) reported that imidacloprid insecticide, applied at 40 mg/kg for 28 days, increased malondialdehyde levels in the rat hypothalamus and pituitary. Our results agree with these previous findings by showing higher OS levels in the pituitary and adrenals in both groups of TBT rats.…”
Section: Discussionmentioning
confidence: 98%
“…Increased acetylcholinesterase activity and calcium levels in the hypothalamus and pituitary of the Wistar rat [119].…”
Section: Chlorpyrifos Carbaryl Imidaclopridmentioning
confidence: 94%